(3QSGdI aj GdefWbs - (3eLghds ((3eMeO Hf MSjf GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3XQa dZh eJYdb HGaJJM hGdHGA UdI hbhdg GHJOGA (B.. (3JYdjdG ddGaJJGM Hg Ohf GdJSjI hNU HPdc eY JCNQg YfgG GaGOI ddNaj hGYQGVG Yf GdLdj hJhFI ddJhajb Hjf GdMOjKjf hjMJed Cf jchf XQaG eSJbQG MGdG (B...s
(3BNQgG (B:s
... (3hdgPG hcdeG UObJ UObJ GdfJjLI ceG aj GddRhejI heJi cPHJ cPHJ ceG aj GdJUajI hGdKdGKjI agh de jNQL eWdbG Yf GdbjGS HbjO dPGJg Hd HGdfXQ Edi fJjLI KGfjI (B... (3hGdJeKHd eY Cfg ehUd Edi GdJUOjbs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3TgGOGJ GdQhGjI (B: s
(3GdELGRGJ h GdSeGYGJ (B:s
Keywords: (3GdadSaI hGdefWbs